2003
DOI: 10.1167/iovs.02-0177
|View full text |Cite
|
Sign up to set email alerts
|

Role of NO in Choroidal Blood Flow Regulation during Isometric Exercise in Healthy Humans

Abstract: These data indicate that NO plays an important role in the regulation of choroidal blood flow during isometric exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
62
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 31 publications
6
62
1
1
Order By: Relevance
“…16 Previous studies have demonstrated a decrease in choroidal blood flow with intravenously administered systemic inhibitors of NOS. 19 , [40][41][42][43][44][45] A decrease in choroidal blood flow might be expected to lead to a reduction in the choroidal pO 2 , as was observed. In the current study, the retinal vascular pO 2 remained relatively constant with NOS inhibition, consistent with previous studies that have reported no change in the retinal blood flow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Previous studies have demonstrated a decrease in choroidal blood flow with intravenously administered systemic inhibitors of NOS. 19 , [40][41][42][43][44][45] A decrease in choroidal blood flow might be expected to lead to a reduction in the choroidal pO 2 , as was observed. In the current study, the retinal vascular pO 2 remained relatively constant with NOS inhibition, consistent with previous studies that have reported no change in the retinal blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…The feasibility of the system for determining pO 2 changes separately in the retinal and choroidal vasculatures was established by varying the fraction of inspired oxygen in rats. Furthermore, because inhibition of nitric oxide synthase (NOS) has been shown to be associated with decreased blood flow in the choroid and, to a lesser degree, in the retinal vascular bed, [16][17][18][19][20][21][22][23][24] this model was also used in the current study to establish the feasibility of our system for measuring chorioretinal pO 2 changes.…”
Section: Introductionmentioning
confidence: 99%
“…33,138 The mechanisms of autoregulation in the human eye are, however, complex and not fully explored. [139][140][141][142][143][144][145][146][147][148] No strategy is currently available to normalize autoregulation in disease states associated with abnormal blood flow regulation in response to changes in perfusion pressure. In addition, the time course of loss of RGCs and decline in blood flow is not fully established.…”
Section: Other Approachesmentioning
confidence: 99%
“…Stable choroidal layer perfusion pressure is associated with vascular resistance controlled by the sympathetic nervous system (20) . Released from the vascular endothelium, endothelin-1 and nitric oxide (NO) also play a role in the adaptation of choroidal vascular resistance (18,21,22) . The choroidal layer has the ability to regulate ocular perfusion pressure (which is 67% above baseline) (21,23) .…”
Section: Discussionmentioning
confidence: 99%
“…Released from the vascular endothelium, endothelin-1 and nitric oxide (NO) also play a role in the adaptation of choroidal vascular resistance (18,21,22) . The choroidal layer has the ability to regulate ocular perfusion pressure (which is 67% above baseline) (21,23) . It has been shown that stable perfusion is produced by ocular vasoconstriction (20) .…”
Section: Discussionmentioning
confidence: 99%